A PARALLEL STUDY OF RHINOGENIC AND ODONTOGENIC MAXILLARY SINUS DISEASE. - Elitsa Deliverska; Martin Rubiev (Peytchinski Publishing, 2012)
Because of its close anatomic relations with nosal and oral cavitis, the maxillary sinus is the place of most frequent inflammatory diseases of all paranasal sinuses. Introduction: The aim of this study was to establish differences in etiology and treatment of rhinogenic and odontogenic maxillary sinusitis. Materials and methods: In this study, we analyzed the etiology, clinical characteristics of the disease, x-ray findings, clinical course and treatment of 188 cases, which were diagnosed and treated as odontogenic or rhinogenic maxillary sinusitis in the Departments of Maxillofacial surgery and Otorhinolaringology - "St. Anna" Hospital, Sofia from 2005 to 2010. Patients were divided according to age and sex. Data was systematized and analyzed. Results: This study clearly showed that rhinogenic diseases of maxillary sinus are three times more frequent than odontogenic diseases. Also the etiology of odontogenic sinusitis most often is due to mistakes in the treatment of the upper teeth (alien corpuses, perforation after extraction), which is completely different from rhinogenic sinusitis. In the surgical treatment of rhinogenic maxillary sinusitis usually endonasal polypectomy was followed by operation according to Caldwell-Luc or functional sinus endoscopy. During the surgical treatment of odontogenic sinusitis the most frequent intervention was surgical plastic of oral-antral communication with mucogingival vestibular flap followed by operation according to Caldwell-Luck what is different from the treatment of rhinogenic sinusitis.Conclusion: Maxillary sinus often suffers from inflammatory diseases and should always be examined carefully by means of anamnesis, clinic exam and x-rays to identify its origin. Upper teeth should be treated carefully in everyday's dental practice to avoid being cause of sinusitis.